Analysis of Gender Bias in Advanced English Teaching Materials (BITL): A Study of the Merdeka Curriculum Textbook - Baiq Helmalya Roshita; Yulia Agustina (Indo Publishing, 2026)
Gender bias in textbooks is an important issue in education that needs to be examined, because teaching materials not only serve as a source of knowledge, but also as a tool that shapes the values, perceptions, perspectives, and behavior of students. An unbalanced representation of men and women in teaching materials can reinforce social stereotypes and patriarchal structures and create an unequal educational environment. This study aims to analyze the existing gender representation in the Advanced English Textbook for the Merdeka Curriculum for Grade XII F2 by examining how the roles, activities, professions, and narratives of men and women are presented. Using a qualitative descriptive method with a content analysis approach based on the nurture perspective, this study identifies forms of marginalization, subordination, stereotypes, symbolic violence, and double burdens that may appear in the book's content. The analysis was conducted systematically on the text, narratives, illustrations, and dialogues to see whether the material represented equality or replicated gender bias. The findings of this study are expected to contribute to the development of more gender-sensitive teaching materials, provide recommendations for educators to implement inclusive learning, and support the creation of a fair educational environment in line with the spirit of the Merdeka curriculum.